Czech Republic : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report, 2012)
This paper presents a financial system stability assessment update for the Czech Republic. The financial system is confronted with a number of growing risks. Owing to a high reliance of the Czech economy on exports to European Union (EU) countries, the main risk stems from negative developments in EU countries. The results of stress tests show that Czech banks can withstand substantial shocks. The paper reports that the regulatory and supervisory framework for financial institutions is generally sound, although inadequate resources are a major weakness.